Tingkat Kepatuhan Penderita Malaria Vivax Dalam Minum Obat Serta Faktor Yang Mempengaruhinya Studi Pada Penderita Malaria Vivax Di Kabupaten Banjarnegara Tahun 2005 - M. Arie Wuryanto (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2008)
Background : Since 2003 until March 2004 malaria cases in Banjarnegara was still high.The proportion of plasmodium vivax more higher ( 60%) than falciparum (40%). It’s mean reflecting incompliance of malaria drug treatment. The study was intended to know level of compliance and identified same factors that related with compliance of malaria drug treatment.Method : This research was used Cross sectional design. Cases were patients of malaria vivax where detected since October 2004 until March 2005. Respondent more than 15 years age, and was used 14 days treatment method. This study was take 120 respondents of malariavivax cases.Result: Malaria vivax cases who incompliance were 64%, it’s mean that level of compliance were 36%. Reason for stopping treatment was caused by feeling healthy of patients after 3 or 5 days of malaria drug treatment. The result of chi-square test showed a significant associationbetween the level of patient knowledge and level compliance of malaria drug treatment (p-value = 0.002, ratio prevalent = 4,8 ( 95% CI: 1,7 - 13,7)). Level compliance of malaria drug treatment was depended on level of patient knowledge. Patient with poor knowledge had 4,8 times to become incompliance of malaria drug treatment.Keyword: Compliance, malaria drug treatment, malaria vivax